Loss of TLR3 and its downstream signaling accelerates acinar cell damage in the acute phase of pancreatitis - Regel, Ivonne; Mihaljevic, Charlotte; Raulefs, Susanne; Benitz, Simone; Rieder, Simon; Leinenkugel, Georg; Steiger, Katja; Schlitter, Anna Melissa; Esposito, Irene; Mayerle, Julia; Kong, Bo; Kleeff, Jörg H.; et al. (Pancreatology, 2019)
Apoptosis; Experimental acute pancreatitis; Necrosis; TRIF; Toll-like receptor 3
Available online 15 December 2018
Gesehen am 05.06.2019